Opportunities And Challenges Of Shari'ah Based Banking In Jember District - Ratih Rachmawati (LPPM Institut Teknologi dan Sains Mandala, 2020)
Shari'ah banking is increasingly recognized in the community from day to day. Not only for Muslims, but also for those who are non-Muslims. Shari'ah banking opportunities in the future are very large. Given, there are many components that support the creation of sound and reliable shari'ah banking. The various supporting components need to be put to good use. The opportunity exists, no matter how small, it will contribute to the development of shari'ah banking. However, the opportunity to become an established shari'ah banking company cannot be separated from various challenges. Whether they come from within, or come from outside. All of these challenges need to be faced, resolved and then find the right solution for the advancement of shari'ah banking. Keywords: Opportunities, Challenges, Shari'ah banking